Association between the number of board-certified cardiologists and the risk of in-hospital mortality: a nationwide study involving the Japanese registry of all cardiac and vascular diseases. Issue 12 (15th December 2019) - Yoneyama, Kihei; Kanaoka, Koshiro; Okayama, Satoshi; Nishimura, Kunihiro; Nakai, Michikazu; Matsushita, Kunihiro; Miyamoto, Yoshihiro; Kida, Keisuke; Ishibashi, Yuki; Izumo, Masaki; Watanabe, Makoto; Soeda, Tsunenari; et al.
Abstract : Objectives: Although there are 14 097 board-certified cardiologists in Japan, it is unknown whether the number of institutional board-certified cardiologists is related to the prognosis of cardiovascular disease patients. Design: Cross-sectional analysis. Setting: Data were collected from the nationwide database of acute care hospitals in Japan (2371 hospitals) between 2012 and 2013. Participants: A total of 1 422 703 consecutive patients were initially included in this study, but 518 610 patients were excluded due to age <18 years, missing data or prior hospitalisations; therefore, 896 171 patients comprised the final sample population. Main outcome measures: The primary outcome was in-hospital mortality due to any cause. For the per-hospital analysis, Poisson regression models were used to estimate the association of board-certified cardiologists with in-hospital mortality, adjusted for hospital facilitation. For the per-patient analysis, hierarchical logistic regression models were used to estimate the ORs of the number of institutional board-certified cardiologists, adjusted for patient demographics, diagnoses, therapies and hospital facilities. Results: The regression model of the per-hospital analysis indicated that the number of board-certified cardiologists was associated with a lower rate ratio of in-hospital mortality (rate ratio, 0.988; 95% CI 0.983 to 0.993; p<0.01). The per-patient analysis indicated that the median age was 73 years and the in-hospital mortality rate was 11.7%. The regression model indicated that the presence of more board-certified cardiologists was associated with a lower risk of in-hospital mortality (OR, 0.980; 95% CI 0.975 to 0.986; p<0.01) after adjustments for hospital facilities, patient characteristics and treatments. Conclusions: Among cardiovascular disease patients admitted to acute care hospitals in Japan, the presence of more board-certified cardiologists was associated with a lower risk of in-hospital mortality. These results have implications for national and institutional strategies for determining the required number of board-certified cardiologists.